Effect of edge preparation when hard turning tool steel - Shaari, Mohd. Rosmani (2010)
Hard turning is a technique that can be used as a substitute to grinding in the finishing operation for hardened steel (45 HRC and above). However, the use o f this technique is limited due to the high cost of the cutting inserts. The developments o f new cutting tools such as ceramic and CBN has made hard turning feasible. This project was undertaken to analyze the effect o f edge preparation (honed, honed with wiper finishing and T-land) when turning DF-3 grade hardened steel with hardness 55 HRC. Various cutting speeds: 100, 155 and 210 m/min and various feed rates: 0.05, 0.13 and 0.2 mm/rev were employed. The process was performed under dry cutting condition and with a constant depth of cut (0.2 mm). The machinablity parameters have been studied were cutting forces, surface roughness and chips form. This study shows that the effect of edge preparation on the surface roughness and cutting forces is statistically significant. Specifically, honed with finishing wiper inserts are able to generate better surface finish compared to T-land and honed inserts. T-land insert gives lower radial force as compared with other types o f cutting edge preparation. Edge preparations were found to have only little impact on the tangential force. Continuous chips were obtained regardless of the cutting conditions employed. The cutting forces and surface roughness models were developed using the two levels full factorial design. Analysis done showed that both mathematical models for cutting forces and surface roughness can be used to predict the machining response with the in limits of cutting conditions investigated.